(untitled) (Scientific journal of the Fergana State University, 2025)
Chitin and chitosan, like many other compounds containing carbon and nitrogen elements, are actively involved in the global cycles of these elements in nature. Chitin has three main sources in nature (shells of crustaceans, cuticles of insects and cell walls of mycelial fungi). As an alternative source to the main raw materials of chitin and chitosan, which are widely used in world practice, chitin (polymorphic form γ, degree of crystallinity 24.80%) was isolated from the May beetle, which is widespread in our country and has a high reproduction rate, and was converted into chitosan (degree of crystallinity 11.30%) with a deacetylation degree of 89.1%. Thermal analysis of these substances revealed that the maximum decomposition temperature of chitin is 365.20 ºC, and that of chitosan is 292.53 ºC, and these values vary depending on the polymorphic form of the chitin substance, the degree of crystallinity, the size of the macromolecule, and the degree of deacetylation of chitosan.